Isolation and characterization of biosurfactant producing and oil degrading Bacillus subtilis MG495086 from formation water of Assam oil reservoir and its suitability for enhanced oil recovery. (December 2018) - Datta, Poulami; Tiwari, Pankaj; Pandey, Lalit M.
Highlights: Seven bacterial strains were isolated from formation water of Assam oil reservoir. B. subtilis MG 495086 resulted crude oil-degrading & biosurfactant producing properties. Optimized surfactin production (6.3 g/L) was achieved using RSM in ex-situ condition. B. subtilis MG 495086 could produce surfactin even in in-situ conditions (80 °C, 90 °C) Due to surface properties, B. subtilis MG495086 was predicted to be utilized for EOR. Abstract: The strains isolated from the formation water were characterized and screened considering their crude oil degradation capability and biosurfactant production ability. The growth kinetics study of isolated Bacillus subtilis MG495086 was carried out by varying growth parameters i.e. carbon source, temperature, pH and salinity. The biosurfactant production was optimized adopting RSM-CCD considering carbon source (1–5%), pH (3–11) and temperature (25–65 °C) as matrix parameters. The optimum biosurfactant production (6.3 ± 0.1 g/L) and the minimum surface tension 29.85 mN/m were obtained after 96 h of incubation under optimal conditions i.e. 3.8% (v/v) of light-paraffin oil as sole carbon source at 62.4 °C and pH 7.7 with the maximum oil degradation capability of 91.3 ± 5%. Critical micelle concentration value of crude biosurfactant was found to be 40 mg/L with high emulsification activity of 72.45 ± 0.85%. The produced biosurfactant was identified as lipopeptide (Surfactin) and characterized using various analytical techniques to establish its suitability for microbial enhanced oil recovery.